Relationship among depression, self-efficacy, and quality of life among students in medical and allied health sciences - Mukhtar, Firdaus; Hashim, Hairul Anuar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2010)

(untitled)
Introduction: This study examined a cognitive model of depression among undergraduate students of medical and allied health sciences. Methods: Participants (N = 279) completed a series of questionnaires related to depression (Beck Depression Inventory-Malay), negative cognitions (Automatic Thoughts Questionnaire-Malay), dysfunctional attitude (Dysfunctional Attitude Scale-Malay), stressful life events (Life Events Survey), self-efficacy (General Self-Efficacy) and quality of life (WHO Quality of Life- BREF). Results: Results of descriptive analysis revealed a higher percentage of severe depression among males when compared to female students. Results of structural equation modeling indicated an adequate fit of the model (x2= 21.29, df = 15, p > .13; GFI = 0.97; CFI = 0.97; RMSEA = .04). Conclusion: The findings also indicated the potential roles of self-efficacy in mediating depression. The results are discussed in terms of self-regulating strategies of managing depression and the roles that university authorities may play in helping students to regulate depression.